Architecture of Systems of Processing and Archiving of Library Content is in Heterogeneous Environment of Institute of Higher Education - Timofeev, B.I.; Timoshin Ю.А.; Yarchenko В.П.; Shust , C.O. (Journal of Information Technologies in Education (ITE), 2009)
The questions of information storage for university scientific libraries in this time remains important direction of creation and development of the service systems of their subscribers and are enough complicated the scientific and technical problems of perspective IT-technologies which are related to the creation of available informative funds and resources for universities specialists. The structures of the archiving data systems and e-libraries digital objects are developed for the level of region and of institute, and also the structures of Data Processing Center of this system are showed. The nodes architecture of such system сoincides with the URAN-network nodes and considerably simplifies co-operation of storage systems components of between itself.